Analisis Yuridis Keberadaan Tim Anti Anarkis Satuan Brimob Polda Bali dalam Mengantisipasi Maraknya Aksi Penjambretan - I Wayan Gede Septihadi; Deli Bunga Saravistha; I Wayan Darmika Suputra (Indra Institute Research & Publication, 2023)
In the presence of developments and economic crises in society, it has implications for an increase in crime, one of which is the act of mugging. In an effort to anticipate street crimes, especially acts of mugging that occur within the jurisdiction of the Bali Police, the Police, especially the Brimob Corps, formed a special unit known as the anti-anarchist team, the Bali Police Mobile Brigade Unit, which has the task of anticipating and dealing with mugging crimes that occur in the jurisdiction of the Bali Police. This study aims to understand the role and function of the anti-anarchist team of the Bali Police Mobile Brigade Unit in anticipating mugging crimes that occur in the jurisdiction of the Bali Police. The type of research used is empirical research using a factual approach and statutory approach plus conducting interviews with informants from the Bali Mobile Brigade Police. The results of the study show the role of the anti-anarchist team of the Bali Police Mobile Brigade Unit in anticipating the crime of mugging, namely carrying out pre-emptive, preventive and repressive police duties. However, it has not been able to run smoothly because there are obstacles including the lack of facilities and infrastructure, human resource factors, cultural factors of people who do not care enough, and acts of omission.